"We Don't Want to Live Like This": The Lived Experience of Dislocation, Poor Health, and Homelessness for Western Australian Aboriginal People. (January 2019) - Martin, Robyn; Fernandes, Christina; Taylor, Cheryl; Crow, Amanda; Headland, Desmond; Shaw, Nicola; Zammit, Simone
Many policy interventions have attempted to address the entrenched disadvantage of Aboriginal Australians 1 ; however, sustained improvement in social, cultural, physical, and emotional well-being is not evident. This disadvantage is compounded by paternalistic practices which do not promote Aboriginal self-determination or empowerment. This article presents the lived experience and voice of Aboriginal Australians spending time in parks in Perth, Western Australia. A community-based participatory action research approach informed by critical Indigenous methodologies involving collaboration between Aboriginal and non-Aboriginal service providers was used. Participants experienced disconnection from kin and country, serious risk to personal safety, homelessness, and problematic health; all related to, and intersecting with, time spent in the parks. The participants' narratives highlight the enduring impacts of colonization, dispossession, and racism. These lived experiences are situated within contexts of rising moral panic from politicians, residents and mass media, and siloed policy and service delivery responses.